2012
DOI: 10.1093/bja/aes091
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis comparing epidural, patient-controlled intravenous morphine, and continuous wound infiltration for postoperative pain management after open abdominal surgery

Abstract: Device-related costs of using CWI for pain management after abdominal laparotomy are partly counterbalanced by a reduction in resource consumption. The cost-effectiveness analysis suggests that CWI is the dominant treatment strategy for managing postoperative pain (i.e. more effective and less costly) in comparison with i.v.-PCA. When compared with EDA, CWI is less costly with almost equivalent efficacy. This economic evaluation may be useful for clinicians to design algorithms for pain management after major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 31 publications
2
32
0
3
Order By: Relevance
“…The weighted mean reductions of 13 and 20 mm in pain at rest and on mobilization scores, respectively, are considered to be clinically meaningful as demonstrated in studies of acute pain in the emergency department setting where the minimum clinically significant difference is reported to be 9-13 mm [29,30]. The magnitude of the reduction for pain at rest is similar to that from an observational study by Tilleul et al [31] which also reported significant reductions of approximately 1.5 cm (or 15 mm) for ropivacaine CWI as compared to intravenous morphine. For all three variables included in the meta-analyses, the overall effect size estimates of ropivacaine versus placebo were greater than 0.8 and thus considered to be large in magnitude [32].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The weighted mean reductions of 13 and 20 mm in pain at rest and on mobilization scores, respectively, are considered to be clinically meaningful as demonstrated in studies of acute pain in the emergency department setting where the minimum clinically significant difference is reported to be 9-13 mm [29,30]. The magnitude of the reduction for pain at rest is similar to that from an observational study by Tilleul et al [31] which also reported significant reductions of approximately 1.5 cm (or 15 mm) for ropivacaine CWI as compared to intravenous morphine. For all three variables included in the meta-analyses, the overall effect size estimates of ropivacaine versus placebo were greater than 0.8 and thus considered to be large in magnitude [32].…”
Section: Discussionsupporting
confidence: 53%
“…In this study [21], overall morphine use was significantly reduced from a mean of 21.8 mg in control patients to 11.5 mg with ropivacaine CWI suggesting that 10 mg morphine-sparing is a meaningful reduction for patients. Using published meta-analyses, Tilleul et al [31] estimated the incidences of PONV for intravenous morphine, CWI, and epidural as 36, 24, and 18%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 CWI may also be more cost-effective than EA. 16 Because of its intuitive simplicity, CWI has been proposed as an attractive alternative to EA after colorectal surgery, although CWI alone may be not sufficient to avoid the need for postoperative opioid. 17 To our knowledge, however, CWI and EA have never been compared within a multimodal enhanced recovery program.…”
mentioning
confidence: 99%
“…Continuing along this venue of argumentation, a recent study on continuous wound installation after laparotomy found that this method was in fact the most cost-effective compared to epidural or systemic therapy (Tilleul 2012). A pre-peritoneal catheter reduced the demand for epidural analgesia after colonic surgery (Ozturk 2011).…”
Section: Analgesic Efficacy Of Truncal Blocks Compared To Epidural Anmentioning
confidence: 99%